Livelihood Strategy of Community Forest Users: A Case from Nawalparasi District - Poudel, Devi Prasad (Nepalese Journal of Development and Rural Studies, 2017)
This paper aims to identify the diversification of livelihood strategies of community forest users of different ecological regions in Nawalparasi district. This paper basically based on primary and secondary sources of information primary information have been collected from focus group discussion, key informant survey and household survey. All the primary data are concerned with forest users of the study area. The forest users of the study area have adopted mainly three types of livelihood strategies i.e. farm based, forest based and off-farm based. The finding of the study shows that livestock farming has occupied major role to achieve the average income from farm based livelihood. The linkages between community forest and livelihood of rural people have been found different in the different ecological regions in the study area. The changing life style of members of community forest users can help to manage the forest and improve the livelihood of rural people with the support of such livelihood options in the study area. Nepalese Journal of Development and Rural Studies Vol. 14 (Joint issue) (1&2), 2017, Page: 21-27